Isolation and Screening of Microorganisms for Their Ability to Reduce the Amount of Cholesterol in a Model System - E. Harmayani; J. N. Sofos; G. R. Schmidt (Indonesian Food and Nutrition Progress, 1998)
he objective of this study was to isolate and screen the ability of microorganisms to reduce the amount of cholesterol in a model system supplemented with cholesterol. The cholesterol-degrading bacteria were isolated from samples of various fats and authentic strains were also used. Analyses were performed to determine the rate of cholesterol degradation in model system, effect of the medium pH on cholesterol reduction, and identification of cholesterol-degrading bacteria. Rhodococcus equi ATCC 21107, Rhodococcus equi ATCC 33706, Leuconostoc cremoris, Serratia maicescens ATCC 13880 and several bacterial isolates from fats were capable of degrading cholesterol in a model system supplemented with pure soluble cholesterol. Morphological and biochemical characteristics revealed that some of the bacterial isolates tentatively classified as belonged to the genus Pseudomonas